INTEL AND AMD CPU COMPARISON - Tabors, Edgars; Pēteris, Grabusts (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The author in this work compares Intel and AMD CPU’s in different price categories. Themes which are discussed is CPU history, characteristics and compared Intel and AMD CPU’s. At the end is conclusions about the Intel and AMD CPU’s advantages un disadvantages.